QUALITY CONTROL OF HYDROCHLOROTHIAZIDE TABLETS MARKETED IN SINOP-MT - M. K. Órfão; J. O. Alves; A. S. Valladão; R. Bonfilio; C. R. Andrighetti; E. B. Ribeiro; D. M. S. Vallladão (Scientific Electronic Archives, 2017)
The thiazide diuretics are of the classes of drugs most frequently used for the treatment of hypertension. Hydrochlorothiazide is the representative of this class and is found in tablet form in doses of 25 and 50 mg. It is marketed in three different categories of drugs: reference, similar and generic. According to the regulator in Brazil, the National Health Surveillance Agency (ANVISA), before pharmaceuticals are released for use, the pharmaceutical industry must meet product quality specifications, but the consumption of counterfeit drugs, contraband or without registration with government laws It is growing in Brazil, which affect the entire drug production chain affecting the health of those who use these medicines. In view of the reported problems about the quality of marketed drugs and being the state of Mato Grosso considered a fake gateway drug, due to its proximity to Bolivia, this study aimed to assess the quality of tablets containing hydrochlorothiazide is already one of the most widely used drugs in the treatment of hypertension in Sinop-MT municipality according local search. Samples from five laboratories that produce hydrochlorothiazide tablets at a dose of 25 mg, and the most market in the municipality of Sinop / MT were analyzed as stablished in the Brazilian Pharmacopoeia. It was found that four of the five samples of drugs in Mato Grosso, performed all the requirements for approval in quality testing, with the exception of a product that has lower hardness values than recommended, which can lead to problems drug presentation as well as directly affect the absorption, bioavailability and action of the therapeutic drug. It was concluded that medicinal products containing hydrochlorothiazide showed adequate quality, ensuring their effectiveness.